Manajemen Penanggulangan Bencana Dalam Konteks Restrukturisasi Organisasi Pasca Otonomi Daerah - PratiwiÂ , PratiwiÂ (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2012)
80% of the geographical area in Indonesia is potentially considered as catastrophe areas. This condition needs more established disaster management bureaucracy. Indonesia has Law No. 24/2007 that regulates about disaster management and disaster bureaucracy. This research was conducted to study the implementation of this law in correlation with local autonomy principal. Case study methodology with structured interview guide was used to describe and analyze how coordination and participation after disaster organizational restructurization. Local autonomy in Indonesia indicated several consequences such as imbalance of power in the coordination and lack of resources, and also limited budget. Instead of problems that faced by local government, this study found an indigenous phenomenon of disaster that can reduce the impact of disasters in Kampung Naga. Several local values in this rural area deserve to be an asset for the dissemination of regional disaster program. In addition, this study offers a polycentric governance coordination mechanisms offered to be one recommendation for the lame command authority, budgeting mechanisms problem and human resources.